50 Fast Dreamweaver MX Techniques - Warner, Janine (Wiley Publishing, 2011)
* Includes techniques for building rollovers, embedding Flash movies, creating dynamic tables, adding cool animations, and much more. * Features 50 fast and easy, but powerful, effects that creative professionals and amateurs alike can achieve almost instantly. * Each technique is fully-illustrated with "before" and "after" shots, and carefully described in step-by-step detail. * The CD-ROM includes work files and finished effects from the book.